1994
DOI: 10.1017/s0043174500084162
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cotton (Gossypium hirsutum) and Soybean (Glycine max) Planting Date on Weed Interference

Abstract: Separate field experiments were conducted for cotton and soybean in 1990 and 1991 to determine the influence of planting date on yield loss due to interspecific interference from entireleaf morningglory and sicklepod and to determine the relative competitiveness of each weed species. Percent soybean yield loss due to weed interference increased as planting date was delayed from early May to early June. Averaged over weed species, yield losses from 1.7 weeds m−1row were 10, 18, and 20% for soybeans planted in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…However, aboveground biomass of emerging common cocklebur was less from July than April or May planted soybean. Klingaman and Oliver (1994) found that soybean yield decreased due to entireleaf morning glory and sicklepod ( Cassia obtusifolia L.) as planting date was delayed from early May to early June. Young et al (2003) found that overall soybean injury by postemergence herbicide was greater with late planting than early planting date in Iowa.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…However, aboveground biomass of emerging common cocklebur was less from July than April or May planted soybean. Klingaman and Oliver (1994) found that soybean yield decreased due to entireleaf morning glory and sicklepod ( Cassia obtusifolia L.) as planting date was delayed from early May to early June. Young et al (2003) found that overall soybean injury by postemergence herbicide was greater with late planting than early planting date in Iowa.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Ipomoea hederacea is a self-compatible annual vine that is believed to have a mixed mating system (Ennos, 1981;Elmore, 1986) due to its ability to produce viable seeds from autogamous fertilizations and hand outcrosses. This species is frequently found in cultivated gardens and disturbed areas and is a serious pest species in agricultural crops such as soybean (Thullen and Keeley, 1983;Klingaman and Oliver, 1996), cotton (Klingaman and Oliver, 1994), and peanuts (Bailey et al, 1999) throughout the southeastern United States. Germination occurs between mid-May and August, and flowering in east-central Alabama (AL) begins in early August.…”
mentioning
confidence: 99%
“…When planting early‐maturing soybean, a preharvest desiccant was needed when large amounts of green weeds were present at harvest (6). Many effective soybean weed control programs have been extensively evaluated in the mid‐South using traditional planting systems (13), but few programs have been evaluated for soybean grown using the ESPS (10) or for May‐planted MG III cultivars that mature in August and subsequently require a shorter growing season.…”
Section: Introductionmentioning
confidence: 99%